Strategi diplomasi publik Pemerintah Korea Selatan terhadap Indonesia melalui Hallyu - Kumalaningrum, Widya Sari (UKInstitute, 2021)
South Korea is an example of a country that realizes the strategic meaning of public diplomacy. Korea uses public diplomacy with the Korean Wave or Hallyu being one of the media. The public diplomacy carried out by South Korea through Hallyu attracted the attention of many groups. Hallyu itself refers to all aspects of South Korean culture, including television dramas, films, music, fashion, hairstyles and cosmetics that spread throughout the world. This paper aims to describe the achievement of state interests through the implementation of public diplomacy. The research method used is normative research using conceptual and historical approaches and using literature study. This paper finds that public diplomacy has succeeded in increasing the popularity of South Korea. The South Korean government then uses this popular culture as a diplomatic strategy.